2018
DOI: 10.1016/j.cois.2018.05.016
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors in arthropod vectors: omics and pharmacological approaches to elucidate ligand-receptor interactions and novel organismal functions

Abstract: Regulation of many physiological processes in animals, certainly those controlled by neuropeptide hormones, involves G protein-coupled receptors (GPCRs). Our work focusing on endocrine regulation of diuresis and water balance in mosquitoes and ticks started in 1997 with the kinin receptor, at the dawn of the omics era. After the genomic revolution, we began work on the endocrinology of reproduction in the red imported fire ant. We will use the template of this comparative work to summarize key points about GPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 81 publications
(104 reference statements)
0
27
0
Order By: Relevance
“…The kinin neuropeptide signaling system is pleiotropic in insects, regulating physiological functions both at the central and peripheral levels. They regulate myotropic and diuretic activities, orchestrate innate behaviors during pre-ecdysis and influence feeding behavior (Veenstra et al, 1997; Kim et al, 2006; Kersch and Pietrantonio, 2011; Schooley et al, 2012; Kwon et al, 2016; Pietrantonio et al, 2018). However, the kinin functions in ticks have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinin neuropeptide signaling system is pleiotropic in insects, regulating physiological functions both at the central and peripheral levels. They regulate myotropic and diuretic activities, orchestrate innate behaviors during pre-ecdysis and influence feeding behavior (Veenstra et al, 1997; Kim et al, 2006; Kersch and Pietrantonio, 2011; Schooley et al, 2012; Kwon et al, 2016; Pietrantonio et al, 2018). However, the kinin functions in ticks have remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe a model study using a forward pharmacological approach to investigate a tick neuropeptide G protein-coupled receptor (GPCR) as potential target for tick control (Figure 1). This receptor, known as leucokinin-like peptide receptor (LKR) (accession AF228521), or myokinin receptor (Holmes et al, 2000, 2003) has been suggested as a promising novel target for pest control (Lees et al, 2010; Audsley and Down, 2015; Guerrero et al, 2016; Pietrantonio et al, 2018). A kinin peptidomimetic is antifeedant and lethal to the pea aphid (Smagghe et al, 2010), prevents the blood feeding to repletion in the kissing bug, Rhodnius prolixus , decreasing the chance of a successful molt (Lange et al, 2016) and triggers avoidance behavior in the mosquito Aedes aegypti when given in a sucrose solution (Kwon et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused on the tick kinin receptor (KR) as a model to explore a neuropeptide GPCR as a novel target for tick control. 29 Our previous reverse functional study demonstrated that female cattle fever ticks in which the KR was silenced exhibited significant reproductive fitness costs, 31 such as delay in feeding to repletion, reduced weight of egg masses and decreased percentage of egg hatching. Therefore, fully inhibiting the function of the tick KR with antagonists could result in similar deleterious phenotypes, and those antagonists could represent 'chemical leads' for novel tick control agents.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropeptides have been studied as potential leads for the development of new, environmentally friendly pest control agents due to their specificity and high activity at very low doses. 29 The generic kinins as well as modified insect kinins have been used to functionally characterize the tick KR. 25,27,30 The tick KR appears to be a promising target because knocking-down its expression in female ticks results in significant reduction of their reproductive fitness.…”
Section: Introductionmentioning
confidence: 99%